The transformative tourism learning model - Bueddefeld, Jill; Duerden, Mat D. (Annals of tourism research, 2022)
This conceptual paper addresses gaps in transformative learning and tourism literature. We argue for a more complete integration of Transformative Learning Theory within tourism literature, in order to better understand tourism learning as both a process and a product. The Transformative Tourism Learning Model is proposed as a framework for understanding how to intentionally plan and design tourism learning experiences with specific learning processes and outcomes in mind. This paper offers a synthesis of transformative literature within tourism contexts and the proposes the Transformative Tourism Learning Model to provide researchers and practitioners with a guiding framework in both the design and analysis for tourism learning and behavior change. •A clear definition of what the term “transformative tourism” means•Effective integration of Transformative Learning Theory into the tourism literature•Proposal of the Transformative Tourism Learning Model•Recommendations for next steps of research in transformative tourism research